Cisco Certified Support Technician CCST Networking 100-150 : official cert guide - White, Russ (Official cert guide series., 2024)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for the CCST Networking 100-150 exam. Well regarded for its level of detail, study plans, assessment features, and challenging review questions and exercises, Cisco Certified Support Technician Networking 100-150 Official Cert Guide helps you master the concepts and techniques that ensure your exam success and is the only self-study resource approved by Cisco. Leading Cisco technology expert and best-selling author Russ White shares preparation hints and test-taking tips, helping you identify areas of weakness, and improve both your conceptual knowledge and hands-on skills.